Determinants of diabetic nephropathy among diabetic patients attending in Tikur Anbesa specialized hospital, Addis Abeba, Ethiopia - Esubalew Tesfahun; Kalkidan Mulatu; Tilahun Deresse; Besufekad Mulugeta (Elsevier, 2024)
Background: Diabetic nephropathy (DN) is the consequence of patients with uncontrolled diabetic mellitus and exposed patients to end-stage renal disease. Even though studies conducted to investigate factors associated with DN but still a need to identify what contributes to its occurrence. Therefore, this study aimed to identify determinants of diabetic nephropathy among diabetic patients. Methods: Institutional-based unmatched case-control study was conducted from April 1st to May 30th, 2023. Systematic random sampling techniques were used. Data were collected using questionnaire. Model fitness was checked by the Hosmer and Lemeshow goodness of model fitness test. In multivariable analysis, a p-value ≤0.05 at a 95% confidence interval was used as declared significant variables. Result: This study included 540 participants (180 cases and 360 controls) with a response rate of 98%. Poor glycaemic control (AOR: 4.58, 95% CI: 2.22-9.48), Body Mass Index (BMI) being overweight (AOR: 13.05, 95% CI: 5.56-30.62), non-adherence to diet (AOR: 7.52, 95% CI: 3.31-17.05), poor healthcare efficiency system-(AOR: 6.67, 95% CI: 3.43-12.97) and long duration of Diabetes Mellitus (DM) after diagnosis (AOR: 4.45, 95% CI: 2.39-8.28) were the determinants of diabetic nephropathy. Conclusion: The determinants of diabetic nephropathy in this study were poor glycaemic control, obese BMI, poor efficiency of the healthcare system, and long duration of DM after diagnosis. Therefore, diabetic patients better emphasize weight reduction and follow strict dietary recommendations also clinicians should address dietary counseling, ensure effective and efficient healthcare service. This research faced the limitation of dietary adherence questionnaire it might be subjective to recall bias.